2005
DOI: 10.1016/j.febslet.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a mutant elongation factor G trapped with a GTP analogue

Abstract: Elongation factor G (EF-G) is a G protein factor that catalyzes the translocation step in protein synthesis on the ribosome. Its GTP conformation in the absence of the ribosome is currently unknown. We present the structure of a mutant EF-G (T84A) in complex with the non-hydrolysable GTP analogue GDPNP. The crystal structure provides a first insight into conformational changes induced in EF-G by GTP. Comparison of this structure with that of EF-G in complex with GDP suggests that the GTP and GDP conformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 41 publications
4
85
0
Order By: Relevance
“…S2A). This finding is not entirely surprising given that the structure of EF-G in nucleotide-free form (PDB ID code 1ELO) is almost identical to that of GTP-(2BV3) and GDP-(2BM0) bound forms (27,29,30). Nevertheless, the structure of isolated BipA bound to GDPCP (a GTP analog) allowed us to delineate the nucleotide-binding site (SI Results).…”
Section: Resultsmentioning
confidence: 93%
“…S2A). This finding is not entirely surprising given that the structure of EF-G in nucleotide-free form (PDB ID code 1ELO) is almost identical to that of GTP-(2BV3) and GDP-(2BM0) bound forms (27,29,30). Nevertheless, the structure of isolated BipA bound to GDPCP (a GTP analog) allowed us to delineate the nucleotide-binding site (SI Results).…”
Section: Resultsmentioning
confidence: 93%
“…The conformation of EF-G bound to FA on the ribosome has been characterized by cryo-EM of ribosome-EF-G complexes stalled by FA (Agrawal et al 1998;Stark et al 2000). Compared to the conformation of unbound EF-G, determined crystallographically (AEvarsson et al 1994;Czworkowski et al 1994;Al-Karadaghi et al 1996;Hansson et al 2005), in the ribosome-bound conformation domain IV of EF-G is tilted relative to the body of the molecule formed of domains I and II. Based on cryo-EM, it has been suggested that the rearrangement of EF-G that is induced by GTP hydrolysis consists of a movement of domain IV.…”
Section: Ribosome Disassembly As An In Vivo Target Of Fusidic Acidmentioning
confidence: 99%
“…However, the question of whether different nucleotides or nucleotide analogs exhibit different properties for assembly of the SRP GTPase complex has not been fully explored. Interaction specific to the analog GMPPNP in a different GTPase was suggested by a structure of an EF-G complex in which a peptide flip within the P-loop directs a carbonyl oxygen towards the β-γ amido group of the analog (Hansson et al, 2005). A peptide flip of the corresponding residue of the P-loop in Ffh is observed as a minor population in structures of the Ffh NG domain determined ultra-high resolution (Ramirez and Freymann, 2006).…”
mentioning
confidence: 99%